2015
DOI: 10.1111/jfbc.12224
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Natural Astaxanthin on the Formulation and Storage of Marinated Chicken Steaks

Abstract: The present study reports on the extraction of astaxanthin from shrimp processing by‐products using corn oil. Its antioxidant activities at different concentrations were evaluated using various antioxidant assays, including DPPH (1,1‐diphenyl‐2‐picrylhydrazyl) radical scavenging (IC50 = 6.3 μg/mL), reducing power, β‐carotene bleaching (IC50 = 20.4 μg/mL) and total antioxidant capacity assays. Interestingly, astaxanthin extract showed strong antioxidant activity. The astaxanthin from shrimp by‐products was adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
(59 reference statements)
1
8
0
1
Order By: Relevance
“…higher rates for CON, SULP and ASC than for AST patties (data not shown). The antioxidant effect of astaxanthin on raw-meat lipid oxidation has been previously assessed by Abdelmalek et al (2016) when adding 10 ppm of astaxanthin to marinated chicken steaks.…”
Section: Refrigerated-stored Fresh Pattiesmentioning
confidence: 99%
See 1 more Smart Citation
“…higher rates for CON, SULP and ASC than for AST patties (data not shown). The antioxidant effect of astaxanthin on raw-meat lipid oxidation has been previously assessed by Abdelmalek et al (2016) when adding 10 ppm of astaxanthin to marinated chicken steaks.…”
Section: Refrigerated-stored Fresh Pattiesmentioning
confidence: 99%
“…To the best of our knowledge, it has been reported that feeding of pigs (Carr, Johnson, Brendemuhl, & Gonzalez, 2010) or chickens (Perenlei et al, 2014) with appropriate doses of this carotene can lead to an improvement in meat colour and oxidative stability. Furthermore, Abdelmalek et al (2016) demonstrated an antioxidant effect of astaxanthin in marinated chicken steaks during refrigerated storage. No studies have been carried out, however, on the effect of astaxanthin on the quality of red meat and specifically that of lamb, which is widely consumed in European Mediterranean countries where light lamb meat is considered a luxury meat (Linares, Bórnez, & Vergara, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…Taksima, Limpawattana, and Klaypradit (2015) encapsulated an astaxanthin-containing lipid extract from shrimp by ultrasonic atomization, using an alginate/chitosan matrix; the lipid extract was effectively encapsulated, and, after addition of the capsules to yogurt, positive acceptance and purchase intent were found in sensory tests. In a more recent work, Abdelmalek et al (2016) developed marinated chicken steaks containing astaxanthin extracted from shrimp by-products and found minimal lipid oxidation during storage, while microbiological quality was preserved.…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados mostraron un efecto colorante de la astaxantina adicionada en las carnes para hamburguesas, disminuyendo la luminosidad y aumentando el valor de a* de forma dependiente de la concentración adicionada. Estos resultados son consistentes con los obtenidos en carne de cerdo picada por Pogorzelska et al (2018) y en filetes de pollo marinados por Abdelmalek et al (2016).…”
Section: 2unclassified
“…To the best of our knowledge, it has been reported that feeding of pigs or chickens with appropriate doses of this carotene can lead to an improvement in meat colour and oxidative stability. Furthermore, Abdelmalek et al (2016) demonstrated an antioxidant effect of astaxanthin in marinated chicken steaks during refrigerated storage. No studies have been carried out, however, on the effect of astaxanthin on the quality of red meat and specifically that of lamb, which is widely consumed in European Mediterranean countries where light lamb meat is considered a luxury meat (Linares, Bórnez, & Vergara, 2007).…”
Section: Introductionmentioning
confidence: 96%